Comparison of Shadowgraphy and X-Ray Phase Contrast Methods for Characterizing a DT Ice Layer in an Inertial Confinement Fusion Target. (2nd October 2020) - Harding, D. R.; Wittman, M. D.; Redden, N. P.; Edgell, D. H.; Ulreich, J.
Abstract: Shadowgraphy and X-ray phase contrast (XPC) imaging are two techniques that are used for characterizing the deuterium-tritium ice layer in inertial confinement fusion targets. Each technique has limitations that affect how accurately they can characterize small crystalline defects and measure the ice thickness nonuniformities that may be only a few micrometers in height. The concern is that shadowgraphy may be overly sensitive to the shape and depth of defects in the ice surface and insufficiently sensitive to the shape of longer wavelength roughness, while XPC may be too insensitive to defects in the ice surface. Multiple ice layers with different thicknesses (40 to 63 μm), thickness uniformities (peak-to-valley variations that range from < 2 to 12 μm), and crystal defects were analyzed using shadowgraphy and XPC techniques. The results from each method agree when the ice layer is uniformly thick and the crystal lacks defects. That agreement worsens as the number of defects in the surface of the ice layer increases, and the roughness (that is determined from a shadowgram image of the target's limb) becomes greater than can be justified by the number of defects that are seen in the target's front and rear surfaces. The XPC technique is considerably less sensitive to surface defects, in part because of the poorer dynamic range and image resolution compared to shadowgraphy. Localized regions of the ice layer that are thicker or thinner than the average thickness of the layer are reported by shadowgraphy to be smaller in height and footprint (by up to 30%) than by XPC. As a result, the two techniques report different ice layer thicknesses that can vary by up to 10%. Shadowgraphy, which results from two caustics that trace different paths through the target, and in theory, image the same ice/vapor surface (but reflect from either the vapor or ice side of the interface), did not consistently characterize the size or shape of ice features to be the same magnitude. The XPC technique provides the best assessment of low-mode (l < 7) roughness in the ice layer. Shadowgraphy results using the strongest caustic is best for detecting the presence of grooves in the ice, although not for quantifying the size of them. If multiple grooves are present, it is best to discard and reform the ice layer.